Hegel's concept of concept and Its relationship to Kant's negative magnitudes and Marx's concept of capital in his capital - Kuyumcuoğlu, Hüseyin Sungur. (My University, 2014)
The relationship between Marx's works on political economy and Hegel's philosophy has been the subject matter of numerous discussions and inquiries. Many of those inquiries take an issue with the relationship between Marx's Capital and Hegel's Logic. In this work, the focal issue is narrowed down to the relationship between Marx's concept of capital in his Capital and Hegel's concept of concept. It is argued here that Marx benefits from Hegel's concept of concept when he defines what capital is and how it works. The inquiry is further expanded with the relationship between Hegel's concept of concept and his concept of essence and the relationship between Hegel's concept of essence and Kant's negative magnitudes. In the overall analysis, I aim to disclose the metaphysical roots of Marx's concept of capital through Kant's negative magnitudes, Hegel's concept of essence and Hegel's concept of concept.